Department of Community Dentistry, Faculty of Dentistry Hasanuddin University Dentist Makassar, Indonesia - Muhammad Ilyas; Clarissa Phielip (Journal of Dentomaxillofacial Science, 2014)
The main objective of caries prevention programs in the community is to reduce the number of colonies of cariogenicbacteria, especially Streptococcus. A method of caries preventionthat is currently developed is a method using probioticsthrough yogurt. This research is a laboratory based experiment using the cross over with control group design. Fifteensamples were collected randomly from a population of preclinical dentistry students of Hasanuddin University fromentry year 2008 until 2010. The results showed a significant difference between before and after drinking yogurt wherethe number of colonies of cariogenic bacteria in saliva reduced (p<0.05)and there is also a significant differencebetween the temperature of the yogurt in reducing the average number of cariogenic bacteria in the saliva after six andnine days yogurt consumption (p<0.05). In addition, there is a significant difference pH of saliva between before andafter drinking yoghurt (p <0.05). It is concluded that drinking yogurt reducts colony of cariogenic bacteria in youngadult saliva